FILLMORE’S SOCIAL DEIXIS FOUND IN DEE’S PERAHU KERTAS NOVEL - DEWANTI, EKA GITA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Pragmatics, Deixis, Social Deixis, Fillmore, Dee, Perahu Kertas Novel. This study analyzed social deixis expressions that were found in Dee’s Perahu Kertas novel. There are some theories that can be used to identify types of social deixis, but Fillmore is the only one who proposed a complete category of it. This study was conducted to find out: (1) the forms of social deixis, (2) the mostly found category of social deixis, and (3) the meaning of each social deictic expression.The writer used qualitative method because the study used words as the data. This study was classified as document analysis because the data that were taken from a novel written by Dee entitled Perahu Kertas.In this study, the writer found 59 social deixis expressions that were categorized into six categories. The data were taken from different utterances that were spoken in six different languages. The mostly found category was honorific category in which 21 expressions found in the novel. Other types of social deixis found in the novel were person marking consisting of 20 words, speech level consisting of 4 words, social acts consisting of 10 words, and also 4 words of linguistic performance. Besides, the writer found no distinction in utterances in the novel. Moreover, the writer revealed the meaning of each social deixis expressions based on information that were given by six informants and also footnote provided by Dee in the bottom of the pages of the novel.The writer hopes that the next researcher has deeper understanding aboutthe theory of deixis that can help them to analyze the data well. Moreover, thewriter suggest for the next researcher to use other theory of social deixis andmedia as the data source.